P637 Targeting mucosal healing: dose optimization of Vedolizumab in IBD patients with inadequate endoscopic response to standard dosing. (30th January 2023) - Dal Buono, A; Gabbiadini, R; Migliorisi, G; Solitano, V; Canziani, L; Repici, A; Armuzzi, A
Abstract: Background: The GEMINI trial assessed improved clinical outcomes after an increase to 4-weekly dosing of Vedolizumab in nearly 40% of patients with insufficient response to standard 8-weekly dosing. However, later real-world data have partially questioned the efficacy of dose optimization due to the early randomization in the study design. The investigation on dose escalation efficacy of Vedolizumab in inflammatory bowel diseases (IBD) remains scarce. We aimed to explore the clinical benefit of Vedolizumab dose escalation every 4 weeks in a cohort of IBD patients with insufficient endoscopic response to the standard dosing regimen. Methods: This is a retrospective single-center study. IBD patients, who showed persistent endoscopic activity (Mayo score ≥ 2 or SES-CD ≥7) with 8-weekly dosing Vedolizumab were included. Clinical data were retrieved from patients' charts. Response after therapy optimization was compared to standard 8-weekley dosing through Wilcoxon signed-rank test for quantitative variables with non-normal distribution; univariate analysis of different factors impacting on therapy response was performed. Results: A total of 52 IBD patients, 30 (57.7%) and 22 (42.3%) with ulcerative colitis and Crohn's disease, respectively, were included. Overall, the median disease's duration at Vedolizumab start was 12.5 month (range 3 36); 31 patients (59.6%) had been previously treated with anti-TNFs. Before Vedolizumab dose escalation 32/52 patients (61.5%) and 20/52 patients (38.5%) showed moderate (Mayo score =2; SES-CD= 7-15) and severe endoscopic activity (Mayo score =3; SES-CD ≥ 15), respectively. We observed a significant reduction of fecal calprotectin from baseline [median 133 μg/g (range 21-3800)] after Vedolizumab optimization [median 77 μg/g (range 6.0-521)] ( p <0.001). After Vedolizumab optimization 28/52 patients (53.8%) obtained further endoscopic response (78.6%) or remission (21.4%) ( p <0.001). At univariate analysis non exposure to anti-TNF and a lower disease duration at Vedolizumab start significantly correlated with endoscopic response after optimization (HR 0.28, 95%CI 0.32 – 0.76, and HR 0.32, 95%CI 0.25 – 0.66, respectively, p <0.001). No adverse events were observed after dose optimization in our cohort. Conclusion: An increase in Vedolizumab dosing frequency is a viable treatment approach for a subset of patients with insufficient endoscopic response standard 8-weekly dosing. Higher response rates might be assessed in anti-TNF naïve patients and with a lower disease duration at therapy start. Prospective studies are needed to confirm these data.